If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -7) + -3x = 4(x + -1) + -1 Reorder the terms: 5(-7 + x) + -3x = 4(x + -1) + -1 (-7 * 5 + x * 5) + -3x = 4(x + -1) + -1 (-35 + 5x) + -3x = 4(x + -1) + -1 Combine like terms: 5x + -3x = 2x -35 + 2x = 4(x + -1) + -1 Reorder the terms: -35 + 2x = 4(-1 + x) + -1 -35 + 2x = (-1 * 4 + x * 4) + -1 -35 + 2x = (-4 + 4x) + -1 Reorder the terms: -35 + 2x = -4 + -1 + 4x Combine like terms: -4 + -1 = -5 -35 + 2x = -5 + 4x Solving -35 + 2x = -5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -35 + 2x + -4x = -5 + 4x + -4x Combine like terms: 2x + -4x = -2x -35 + -2x = -5 + 4x + -4x Combine like terms: 4x + -4x = 0 -35 + -2x = -5 + 0 -35 + -2x = -5 Add '35' to each side of the equation. -35 + 35 + -2x = -5 + 35 Combine like terms: -35 + 35 = 0 0 + -2x = -5 + 35 -2x = -5 + 35 Combine like terms: -5 + 35 = 30 -2x = 30 Divide each side by '-2'. x = -15 Simplifying x = -15
| 3x-4x-8x=10x-8 | | 4x-4+2y=0 | | (x+4)(3x-4)=448 | | 9h+4-7=14 | | 5+0.09x=13.19 | | (x-2)(x-4)(x-6)=40x | | 5+9x=13.19 | | P=4x+36 | | 7c-(8)-(2c)=17 | | 3.2(x+4)+2.7x=5.4(x+2) | | 2/13, | | 3x-7=4(2-x)-1 | | 7c-8-2c=8 | | 0=4800-560x+12x^2 | | 4z-6=(6z+2) | | 12x^2-150+x=0 | | 6+4x+1-2x=-7+3x+9-2x | | 7c+4d-c-3d= | | (1.2*10^-2)=(x^2)/(0.01-x) | | 22-3f=15m | | P(t)=-t^4+72t^2+225 | | 14.99+0.82x=165.87 | | 2x+3y+6x+5y= | | (2x-5)(7x+8)=0 | | -10=10(k-8) | | A=m+mrt | | 2x^3-16x^2-40x=0 | | 2y+6x=108 | | 15x+6(x+4)=255 | | 2x+15+2x-3=57-3x+39 | | 7x+12=12x+32 | | 8n+64=15n-2 |